Autism spectrum disorder in children with Type 1 diabetes. Issue 10 (25th July 2019) - Bethin, K. E.; Kanapka, L. G.; Laffel, L. M.; Majidi, S.; Chaytor, N. S.; MacLeish, S.; Adams, R.; Foster, N. C.; ,
What's new?: Type 1 diabetes and autism spectrum disorder are common chronic diseases that present in childhood; their combined presence adds challenges to care. This is the first large study of the co‐existence of both diseases in the USA. The data demonstrate a frequency of autism spectrum disorder in participants in a large national diabetes database that is similar to that in the general population. Further research on the effect autism has on the management of diabetes is needed. Abstract: Aim: Links between autism spectrum disorder (ASD) and autoimmune diseases, including Type 1 diabetes have been proposed. This study assessed the frequency of ASD in children with Type 1 diabetes in the T1D Exchange (T1DX) registry and the impact of ASD on characteristics of children with Type 1 diabetes. Methods: Analysis included 10 032 participants aged < 18 years (median Type 1 diabetes duration 6.5 years, 48% female, 77% non‐Hispanic White). Diagnosis of ASD was defined as autism, Asperger's or pervasive developmental disorder. Results: A diagnosis of ASD was recorded for 159 (1.58%) participants. Those with ASD were predominantly male (88% vs. 51% of those without ASD, P < 0.001) and slightly older (median 14 vs. 13 years, P = 0.022). Occurrence of diabetic ketoacidosis at Type 1 diabetes diagnosis was similar (35% vs. 41%, P = 0.161). Pump use was lower in those with ASD (51% vs. 63%, P = 0.005) but continuous glucose monitor use was similar (24% vs. 27%, P = 0.351). Median HbA1c was slightly lower in those with ASD [68 vs. 69 mmol/mol (8.4% vs. 8.5%), P = 0.006]. This difference was more pronounced after adjusting for confounders. Conclusions: The frequency of ASD in the T1DX registry was similar to that in the general population. These data show that despite deficits in communication, occurrence of diabetic ketoacidosis was similar in youth with and without ASD. Pump use was less frequent in those with ASD, possibly due to sensory issues, although CGM use did not differ. The lower HbA1c may be due to a more regimented routine with ASD. Because comorbidities such as ASD complicate care of patients with Type 1 diabetes, further research is needed to support these children.